2017
DOI: 10.4103/ortho.ijortho_46_16
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery protocol and hidden blood loss in patients undergoing total knee arthroplasty

Abstract: Background:Perioperative blood loss and postoperative pain following total knee arthroplasty prevent early mobilisation of patients. The Enhanced Recovery Protocol (ERP) followed for patients in our institute aims at reducing post operative pain, blood loss and length of stay.Materials and Methods:50 consecutive patients that underwent ERP following total knee arthroplasty with another group of 70 patients that underwent the same surgery without ERP were compared in terms of hidden blood loss and length of hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…19 Dhawan et al in their consecutive study found female predominance in both group but average age 72 for males and 69 for females in group 1(NON ERP) and in group 2 (ERP) average age for male and female was 71 years, which is different from our study. 20 Hertog et al in their randomized prospective study had predominace of female in both groups and average age of 68.25 in control group and 66.58 in fast track group. 21 The minimum length of stay of our study was 4 days and maximum length of stay was 9 days for group I with mean length of stay 5.69.…”
Section: Discussionmentioning
confidence: 93%
“…19 Dhawan et al in their consecutive study found female predominance in both group but average age 72 for males and 69 for females in group 1(NON ERP) and in group 2 (ERP) average age for male and female was 71 years, which is different from our study. 20 Hertog et al in their randomized prospective study had predominace of female in both groups and average age of 68.25 in control group and 66.58 in fast track group. 21 The minimum length of stay of our study was 4 days and maximum length of stay was 9 days for group I with mean length of stay 5.69.…”
Section: Discussionmentioning
confidence: 93%
“…This study is in contrast with the finding that a solution of bupivacaine with epinephrine similar to the one used in the current study reduce blood loss in total knee arthroplasty [ 18 ]. Generally, solutions containing adrenaline were found to reduce perioperative blood loss in total knee arthroplasty [ 10 , 19 , 20 ], with some exceptions [ 11 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study and participant characteristics of the 49 included studies as well as a description of the shortstay and usual care groups are shown in Table 1. They were published from 2005 to 2023 and originated from sixteen countries: thirteen from the United Kingdom (UK) [25][26][27][28][29][30][31][32][33][34][35][36][37], seven from the United States (US) [38][39][40][41][42][43][44], four from China [45][46][47][48], three studies each from France [49][50][51], Italy [52][53][54] and the Netherlands [55][56][57], two studies each from Canada [58,59], Denmark [60,61], New Zealand [62,63], and Sweden [64,65], and one study each from Australia [66], Brazil [67], Germany [68], India [69], Ireland …”
Section: Trial Design Setting and Characteristicsmentioning
confidence: 99%